GRID-PARAMETER OPTIMIZATION OF DISCRETE SYSTEMS WITH PHASE CONTROL - A. A. Lobaty; L. V. Rusak; M. A. Al-Mashhadani (Системный анализ и прикладная информатика)
Solved the problem of determining the optimal values of the parameters of a discrete system with phase control, for which the minimum of a given functional quality. Obtain the solution in general and implemented on a specific example of a system that has a specified transfer function.